2017
DOI: 10.1007/s11060-017-2481-1
|View full text |Cite
|
Sign up to set email alerts
|

The Simpson grading in meningioma surgery: does the tumor location influence the prognostic value?

Abstract: In meningiomas, location-specific differences of the prognostic value of the Simpson classification are sparsely investigated but can influence strategy of surgery. We therefore compared the prognostic value of the Simpson classification in different tumor locations. Progression was compared with Simpson grade in 826 meningioma patients (median age 58 years, female:male ratio 2.4) in location-specific uni- and multivariate analyses. Simpson grade strongly correlated with tumor location (p < .001). Within a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 40 publications
5
66
0
Order By: Relevance
“…This represents a 1% risk of surgical retreatment per patient-year of follow-up. Patient-and tumor-characteristics were similar to previous studies reported in the literature 15,16 . However, the recurrence rate was significantly lower than in previously reported data 5,16 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This represents a 1% risk of surgical retreatment per patient-year of follow-up. Patient-and tumor-characteristics were similar to previous studies reported in the literature 15,16 . However, the recurrence rate was significantly lower than in previously reported data 5,16 .…”
Section: Discussionsupporting
confidence: 83%
“…Patient-and tumor-characteristics were similar to previous studies reported in the literature 15,16 . However, the recurrence rate was significantly lower than in previously reported data 5,16 . This is especially noteworthy as we have a high proportion of skull-base meningiomas in our overall cohort (47%).…”
Section: Discussionsupporting
confidence: 83%
“…This was not surprising; these are all WHO grade I cranial base tumors; there is abundant literature that substantiates the impact age, Simpson's grade, and PR receptor status have on tumor recurrence. [39][40][41] Our cohort was reflective of the usual reported pattern of WHO grade I cranial base meningiomas; 72% of the patients were female and the average age was 61.8 years. The PR receptor status was also consistent with that reported for WHO grade I cranial base meningiomas; among the 234 patients, in whom this information was available, 96% were PRþ.…”
Section: Discussionmentioning
confidence: 93%
“…This fact justifies the recommendation made by Sughrue et al 6 to be no aggressive in the resection of small tumor remnants in skull base meningiomas if this significantly increases the risk of neurological deficits for the patient. However, recently Voss et al 7 show that Simpson's grading and extent of resection were not similarly important in all locations. It is remarkable that the recurrence in the SWMs has been reported in the literature as very high.…”
Section: Discussionmentioning
confidence: 96%
“…In medial meningiomas the recurrence rate at 10 years varies between 30% and 100% of cases, where the rates of complete resection of the meningiomas of this location are very low in the historical series, between 60% and 85%. 7 On the other hand, the new 2016 WHO classification modifies the diagnostic criteria for grade II meningiomas and with these criteria some grade I tumors have one or more pathological criteria for grade II meningiomas. 2 In our series, cases of grade I meningiomas showing a rapid growth is not exceptional, as well as regional recurrences or the synchronic presence of multiple lesions.…”
Section: Discussionmentioning
confidence: 99%